The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12916-020-01574-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of conflict during the Ebola outbreak in the Democratic Republic of the Congo 2018–2019

Abstract: Background: The 2018-2019 Ebola virus disease (EVD) outbreak in North Kivu and Ituri provinces in the Democratic Republic of the Congo (DRC) is the largest ever recorded in the DRC. It has been declared a Public Health Emergency of International Concern. The outbreak emerged in a region of chronic conflict and insecurity, and directed attacks against health care workers may have interfered with disease response activities. Our study characterizes and quantifies the broader conflict dynamics over the course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 19 publications
4
27
0
2
Order By: Relevance
“…The authors found that African researchers are significantly under-represented in the global health community, even when the data originates from Africa. A common threat is parachute-research, in which non-African researchers benefit from data sharing and open data, are afforded the opportunity to narrate African stories (in some cases also contributing to deficit narratives), and publish scientific work using African generated data available through open access initiativesall while ignoring the contributions of African communities and scholars [66,74,82,127]. Recent work within the medical sciences published on the Ebola outbreak in the Democratic Republic of the Congo can be cited as a prime example in this regard.…”
Section: Resource Inequalities and Colonial Oppressive Histories Instillmentioning
confidence: 99%
“…The authors found that African researchers are significantly under-represented in the global health community, even when the data originates from Africa. A common threat is parachute-research, in which non-African researchers benefit from data sharing and open data, are afforded the opportunity to narrate African stories (in some cases also contributing to deficit narratives), and publish scientific work using African generated data available through open access initiativesall while ignoring the contributions of African communities and scholars [66,74,82,127]. Recent work within the medical sciences published on the Ebola outbreak in the Democratic Republic of the Congo can be cited as a prime example in this regard.…”
Section: Resource Inequalities and Colonial Oppressive Histories Instillmentioning
confidence: 99%
“…a las personas por la degradación de servicios ecosistémicos, por ejemplo, mediante cambios en la hidrología, la gestión del agua, y la agricultura de regadío (Recuadro 1) 52 . También es posible que las relaciones a gran escala entre brotes de enfermedades zoonóticas y conflictos armados, como se documentó para el Ébola en la República Democrática del Congo en 2018-2019 53 , puedan verse influenciadas por el deterioro ambiental concomitante con ambos.…”
Section: A Síntesis De Los Datos Actualesunclassified
“…Les impacts de la guerre sur les écosystèmes incluent également les coûts indirects imposés aux populations par la dégradation des services écosystémiques, comme par exemple au travers de changements dans l'hydrologie et la gestion de l'eau ou l'agriculture irriguée associées (Encadré 1) 52 . Il est également possible que des relations à grande échelle entre épidémies de zoonoses et conflits armés puissent être influencées par la détérioration de l'environnement liée à ces deux aspects, comme cela a été documenté pour le virus Ébola en République démocratique du Congo, en 2018-2019 53 .…”
Section: Figuresunclassified